1978
DOI: 10.1111/j.1348-0421.1978.tb00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Induction in Experimental Animals by Clinical Strains of Streptococcus mutans Isolated from Japanese Children

Abstract: Oral implantation and the cariogenic activity of clinical strains of Streptococcus mutans which had been isolated from Japanese children and labeled with streptomycin-resistance were examined in specific pathogen-free Sprague-Dawley rats. All the seven strains tested were easily implanted and persisted during the experimental period. Extensive carious lesions were produced in rats inoculated with clinical strains of S. mutans belonging to serotypes c, d, e, and f, and maintained on caries-inducing diet #2000. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
1
1

Year Published

1980
1980
1997
1997

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 30 publications
(23 reference statements)
3
32
1
1
Order By: Relevance
“…In addition, the pH of the culture broth of heterofermentative lactobacilli is generally higher than that of homofermentative cultures, indicating less acidogenicity of the former. In our previous study, L. fermentum YIT 82R was shown to be noncariogenic in SPF rats fed diet 2000 for 89 days (12). Furthermore, L. fermentum TY 1 R used in this study did not induce significant dental caries in normally-salivated SPF rats fed diet 2000 (unpublished data).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In addition, the pH of the culture broth of heterofermentative lactobacilli is generally higher than that of homofermentative cultures, indicating less acidogenicity of the former. In our previous study, L. fermentum YIT 82R was shown to be noncariogenic in SPF rats fed diet 2000 for 89 days (12). Furthermore, L. fermentum TY 1 R used in this study did not induce significant dental caries in normally-salivated SPF rats fed diet 2000 (unpublished data).…”
Section: Discussionsupporting
confidence: 55%
“…carry any type of mutans streptococci in their indigenous oral microflora. The normally-salivated rats, therefore, could not induce significant dental caries when they are fed caries-inducing diet 2000 (12,24). In addition, no mutans streptococci could be detected from either the normally-salivated rats or the hyposalivated rats with rampant dental caries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. mutans MT8148R (serotype c), which had been isolated from a carious lesion of a Japanese child and made streptomycin resistant, was used in the present study. The time schedule of the experiment, the experimental procedures, and the maintenance of the exprimental animals were described in the previous papers (Hamada et al, 1978;Ooshima et al, 1981Ooshima et al, , 1983. The basic experimental diet used in this study was cariogenic diet #2000 containing 56% sucrose (Keyes and Jordan, 1964).…”
mentioning
confidence: 99%
“…2 ~ 4) Mutans streptococci are accepted to be one of the microorganisms responsible for dental caries, and their cariogenicity depends on the availability of sucrose. 5 ) Therefore, it has been suggested that one major method for preventing dental caries is to control sucrose consumption. Several investigators have examined the possibility of substituting sucrose by non-cariogenic sugars or sugar alcohols.…”
mentioning
confidence: 99%